2018
DOI: 10.1136/bcr-2017-223506
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the NERDS syndrome

Abstract: A 22-year-old man presented with symmetric polyarthritis, pruritus and deviation of angle of mouth to the right side since the last 7 years. His symptoms were persistent despite receiving ayurvedic medications and symptomatic therapy. Examination revealed dry skin, cutaneous nodules, xanthelasma, periarticular non-tender swellings, pitting oedema of hands and feet and lower motor neuron type right facial palsy. Haematological investigations revealed eosinophilia and skin biopsy had cutaneous eosinophilic infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Differential diagnosis considered for the patient with arthritis and eosinophilia was summarized. 4 It has been reported that some drugs cause drug-induced hypersensitivity syndrome with eosinophilia and arthritis. 5 However, our patient did not take any medicine before experiencing symptoms of eosinphilic arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential diagnosis considered for the patient with arthritis and eosinophilia was summarized. 4 It has been reported that some drugs cause drug-induced hypersensitivity syndrome with eosinophilia and arthritis. 5 However, our patient did not take any medicine before experiencing symptoms of eosinphilic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient did not have allergies or helminthic infections. Differential diagnosis considered for the patient with arthritis and eosinophilia was summarized 4 . It has been reported that some drugs cause drug‐induced hypersensitivity syndrome with eosinophilia and arthritis 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Swelling of hands or feet and osteoarticular pain result from nodules of tenosynovium. In the peripheral blood elevated values of IgE and eosinophil-derived proteins are noted [ 68 ]. Moreover, when eosinophilia and angioedema occur, two entities with different pathophysiology should be considered – the episodic angioedema with eosinophilia syndrome (Gleich’s syndrome) and non-episodic angioedema with eosinophilia [ 69 ].…”
Section: Causes Of Secondary Hypereosinophiliamentioning
confidence: 99%